New insights into southern ocean physical and biological processes revealed by instrumented elephant seals - Charrassin, Jean-Benoît; Roquet, Fabien; Park, Young-Hyang; Bailleul, Frédéric; Guinet, Christophe; Meredith, Michael; Nicholls, K; Thorpe, Sally; McDonald, Birgitte; Costa, Daniel; Tremblay, Yann; Goebel, Michael; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
In recent years, the international “Southern Elephant seals as Oceanographic Samplers” (SEaOS) project has deployed miniaturized conductivity-temperature-depth satellite-relayed data loggers (CTD-SRDL) on elephant seals 1) to study their winter foraging ecology in relation to oceanographic conditions, and 2) to collect hydrographic data from polar regions, which are otherwise sparsely sampled. We summarize here the main results that have been published in both science components since 2003/2004. Instrumented southern elephant seals visit different regions within the Southern Ocean (frontal zones, continental shelf, and/or ice covered areas) and forage in a variety of different water masses (e.g. Circumpolar Deep Water upwelling regions, High Salinity Shelf Water), depending on their geographic distribution. Adult females and juvenile males from Kerguelen Is. forage pelagically in frontal zones of the Southern Indian Ocean, while adult males forage benthically over the Kerguelen Plateau and the Antarctic Continental Shelf, with the two groups feeding at different trophic levels as shown by stable isotopes analysis. Oceanographic studies using the data collected from the seals have, to date, concentrated on circumpolar and regional studies of the Antarctic Circumpolar Current (ACC) circulation. The temperature and salinity profiles documented by elephant seals at high latitudes, including below sea ice, have permitted quasi-circumpolar mapping of the southernmost fronts of the ACC. By merging conventional data and the high temporal and spatial resolution data collected by seal-borne SRDLs, it has been possible to describe precisely 1) the large-scale features of the ACC in the South Atlantic and its variability; 2) the circulation pattern over the Kerguelen plateau, revealing that the poorly known Fawn Trough concentrates an important proportion of the ACC flow in that region. Seals that foraged in ice covered areas have made eulerian time series available that have allowed for the estimation of sea ice formation rates, a parameter that is otherwise difficult to obtain, while also providing a unique description of the wintertime ocean circulation over the central Weddell Sea continental shelf. Finally, we present the first data collected by a newly-developed fluorescence sensor that as been embedded in the regular CTD-SRDL and deployed on elephant seals at Kerguelen. The fluorometer data obtained have offered the first synoptic view of the 3 dimensional distribution of temperature, salinity and fluorescence over a vast sector of the Southern Indian Ocean, allowing us to describe both vertical and horizontal variations in chlorophyll. This paper will make a core contribution to the Plenary Sessions 2C, 3A and 4A, and will be relevant to 2A and 2B.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin zoologi; oseanografi

To slags minkehval i Antarktis = Two kinds of minke whale in the Antarctic - Williamson, Gordon R (Norsk hvalfangst-tidende, 1961)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Gjenfundne hvalmerker i den antarktiske fangstsesong 1959/60 = Whale marks recovered in the Antarctic whaling season 1959/60 - Brown, S G (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Gjenfundne hvalmerker i sesongene 1955/56 og 1958/59 i Antarktis og i Syd-Afrika i 1958 og 1959 = Whale marks recovered in the Antarctic seasons 1955/56, 1958/59, and in South Africa 1958 and 1959 - Brown, S G (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Spermhvalens forekomst i Sydishavet og månens eventuelle innflytelse på forekomstene = Occurrence of the sperm whale in the Antarctic and the possible influence of the moon - Holm, John L; Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nytt funn av sverd fra sverdfisk (Xiphias gladius) i blåhval (Balaenoptera musculus) i Sydishavet = New find of sword from swordfish (Xiphias gladius) in blue whale (Balaenoptera musculus in Antarctic - Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; fisker; hvaler; marin zoologi; zoologi

Hvalmerking utført av norske hvalbåter i Antarktis i sesongene 1956/57 og 1957/58 : whale marking carried out by Norwegian catchers in the Antarctic, seasons 1956/57 and 1957/58 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvalfangst; marin zoologi

Gjenfunne hvalmerker i den antarktiske sesong 1957/58 = Whale marks recovered during the Antarctic whaling season 1957/58 - Brown, S G (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Undersøkelser av knølhvalen (Megaptera nodosa) i Bellingshausenhavet = Studies on the humpback whale (Megaptera nodosa) in the Bellingshausen Sea - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Gjenfunne hvalmerker i Antarktis i sesongen 1956/57 = Whale marks recovered during the Antarctic whaling season 1956/57 - Brown, S G (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Er det ønskelig og forsvarlig å utvide sesongen for fangst av knøl i Sydishavet? = Is it desirable and justified to extend the open season for humpback whaling in the Antarctic? - Jonsgård, Åge; Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; marinbiologi

Rapport om hvalmerking utført av norske hvalbåter i Antarktis i sesongen 1955/56 = Report on whale marking carried out by Norwegian catchers in the Antarctic season 1955/56 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ash, C E (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nylig gjenfunne hvalmerker = Whale marks recently discovered - Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvaler; marin zoologi

Foreløpige beregninger av den sydlige bestand av store bardehval = Preliminary estimates of the southern populations of the larger baleen whales - Mackintosh, N A; Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ottestad, Per (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Vet vi noe om bestanden av finnhval i Sydishavet? = Do we know anything about the stocks of fin whales in the Antarctic? - Ruud, Johan T (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Om størrelsen på den antarktiske finnhvalbestand sett i relasjon til fangstens størrelse = On the size of the Antarctic fin whale stock relative to the size of the catch - Symons, H W; Mackintosh, N A; Brown, S G; Salvesen, H K (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Beregninger av den sydlige bestand av store bardehval = Estimates of the southern populations of the larger baleen whales - Vangstein, Einar (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; marin zoologi

Nylig gjenfunne hvalmerker = Whale marks recently recovered - Mackintosh, N A (Norsk hvalfangst-tidende, 1955)
Keywords: Sørishavet; hvaler; marin zoologi

Finn- og blåhvalenes trekk i Antarktis = The movements of fin and blue whales in Antarctic waters - Brown, S G (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; hvaler; marin zoologi

Finnhval (Balaenoptera physalus) med 6 fostre = Fin whale (Balaenoptera physalus) with six foetuses - Jonsgård, Åge (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; marin zoologi

Finnes det et fredningsfelt for bardehval i Antarktis? = Does there exist a sanctuary for baleen whales in the Antarctic? - Schubert, Kurt (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nylig gjenfundne hvalmerker = Whale marks recently recovered (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; hvaler; marin zoologi

Undersøkelser over blåhvalens alder i de antarktiske pelagiske fangster 1945/46 - 1948/49 = Investigations of the age of the blue whales in the Antarctic pelagic catches 1945/46 - 1948/49 - Ruud, Johan T (Norsk hvalfangst-tidende, 1950)
Keywords: Sørishavet; hvaler; marin zoologi

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

Hvalmaalinger i Rosshavet (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

A new Antarctic expedition - Darnley, Rowland (Norsk hvalfangst-tidende, 1923)
Keywords: Sørishavet; ekspedisjoner; hvaler; marin zoologi